Influence Of Workload And Job Satisfaction Of Pharmaceutical Workers On The Achievement Of Quality Indicators With Motivation As Intervening Variables In Jakarta Dharmais Cancer Hospital - Gina Fadhilah; Kemala Rita Wahidi; Endang Ruswanti (Jurnal Health Sains, 2022)
Based on an initial survey of 10 pharmacists, there are still many employees (10%) who complain of being tired when the office, especially the morning service, sometimes doesn't have time to rest, eat, plus pharmacists who don't come because of illness, causing the workload to be more The survey results also showed 50% of employees expressed job dissatisfaction this was related to salary provision, relationships with superiors and job placements were not in accordance with their skills and abilities. In addition, 20% of employees show low work motivation, this is because the work environment is not conducive and the workload is high. In addition to the results of observations based on the RSKD suggestion box, the phenomenon of complaints felt by 3 patients / families, including "long pharmacy service, employees do not smile and behave rudely". Long waiting time is one of the components that have the potential to cause patient dissatisfaction. Objective: To analyze the effect of workload and job satisfaction on the achievement of quality indicators with motivation as an intervening variable for pharmacists at Dharmais Cancer Hospital. The research design that will be used in this research is a quantitative approach research model. Quantitative model is a decision model that uses numbers. In addition, based on numerical or numerical data and decision models produce decision variables in the form of numbers with a cross sectional approach. There is a significant effect between workload on the motivation of pharmacists at Dharmais Cancer Hospital, There is a significant influence between job satisfaction on the motivation of pharmacists at Dharmais Cancer Hospital, There is a significant influence between workload on the achievement of quality indicators in the Home Pharmacy Installation Dharmais Cancer. , There is a significant effect between job satisfaction on the achievement of quality indicators in the Pharmacy Installation of Dharmais Cancer Hospital., There is a significant influence between workload and job satisfaction on the achievement of quality indicators with motivation as an influential factor in the Pharmacy Installation of Dharmais Cancer Hospital